What if Life Were Black and White: An Interview with Behjat Omer Abdulla. (11th November 2022) - Omer, Behjat; Abdullah, Meriwan
Abstract : Artist Behjat Omar Abdulla discusses his most recent projects, What if Life is Black and White and From a Distance . These works focus on reflecting on identity, belonging, migration, and citizenship, along with the founding of Abdulla's River of Light project.